Gender Dynamics in Roles, Resources, Control, Decision Making and Household Welfare in Ghana: Implications for Agricultural Sustainability - Amoako, Prince Kwadwo; Ayerakwa, Margaret Frimpong; Tham-Agyekum, Dr Enoch Kwame (International Journal on Food, Agriculture and Natural Resources, 2025)
This study investigates the gender dynamics in cocoa farming households across the Ashanti and Western South regions, focusing on their implications for agricultural sustainability. Using a cross-sectional survey design, data were collected from 401 cocoa farmers through structured questionnaires. Data was analysed using descriptive (frequency, percentage) and inferential statistics (independent samples t-test). Results indicate that men dominate physically demanding tasks such as land preparation (82.8%) and pesticide application (85.0%). In comparison, women are more involved in less intensive tasks like drying cocoa beans (33.2%) and reproductive roles such as food preparation (74.6%). Men control essential resources, including land (82.3%), capital (78.6%), and agricultural tools, while women have greater control over processing resources like drying mats (20.4%). Decision-making is similarly male-dominated, with men leading in areas like farming inputs (82.0%) and household security (85.5%), although women exert influence in daily food decisions (42.4%). Despite these disparities, no significant gender-based differences were found in outcomes for yield, income, or food security. The study highlights the need for gender-inclusive policies and targeted interventions to promote equitable access to resources, enhance women's decision-making capacity, and encourage their involvement in sustainable cocoa farming.